Paradoks representasi kiai dan politik gender dalam novel Indonesiamasa reformasi - Marwata, Heru (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This article aims to explain the paradox of the representation of the kiai (Islamic scholar/cleric) in Indonesian novels during the Reformation era, particularly in relation to gender politics. The 1998 Reformation not only shifted the national political configuration but also influenced the legitimacy of religious authority, including the regulation of women's bodies and agency. This study employs a qualitative approach through critical textual analysis of four novels: Perempuan Berkalung Sorban, Ayat-Ayat Cinta, Negeri 5 Menara, and Kiai Tanpa Pesantren. The theoretical framework utilizes Stuart Hall’s theory of representation, specifically the encoding–decoding model, to examine hegemonic, negotiated, and oppositional positions of meaning within the construction of the kiaifigure. The results indicate that the kiaiis paradoxically represented as both a moral protector of women and a symbolic agent maintaining hierarchical gender structures. Post-Reformation social transformation has not dissolved religious authority but rather encouraged it to adapt into more moderate, disciplinary, or charismatic-cultural forms. This paradox underscores that literature functions as a symbolic arena where the relations between religion and gender are simultaneously produced, maintained, and contested within contemporary Indonesian Muslim society.